Online English Grammar Instruction Using Polysynchronous Approach During Pandemic Times - Nina Inayati; Suparto Suparto; Dwi Mawan Karifianto (Langkawi: Journal of The Association for Arabic and English, 2022)
The purpose of this study is to report the best practices in online grammar learning through the polysynchronous learning model, as well as to explore students' perceptions of such learning model. This study is a descriptive case study covering the design of an online course carried out during the Covid-19 pandemic as the research object. The data processed were in the form of teacher reflections, documents of teaching materials and activities in the Learning Management System (LMS), and an open survey to explore students’ perceptions. The findings from this study indicate that the online grammar learning carried out had sufficient relevance to the concept of polysynchronous learning, which is considered appropriate to be implemented during and after the Covid-19 pandemic. For students' perceptions, in general, they expressed appreciation for the learning process, especially in terms of the personal touch and the teaching style carried out by the teacher, the learning activities, and the teaching materials. Furthermore, some constructive suggestions were also given by students, for example, in the area of overcoming technical problems and learning management. The practices presented in this paper are expected to be useful for other foreign language teachers and lecturers as a form of collective sharing to face the challenges of the online grammar learning process during and after the pandemic.